Xenopus paraxis homologue shows novel domains of expression - Carpio, Ronald (2004)
The paraxis gene encodes a basic helix-loop-helix transcription factor that is expressed in paraxial mesoderm and whose mutant displays an inability to form epithelial somites. Here, the molecular characterization of Xenopus paraxis is reported. paraxis is expressed in the paraxial mesoderm and somites but is down-regulated during muscle differentiation. In addition to its paraxial mesodermal expression, described in other organisms, two novel expression domains of paraxis were found: the neural tube and the head mesoderm, paraxis expression in the neural tube was compared with the expression of the neural markers Xash and Xiro1, and we concluded that paraxis is expressed in a broad band in the prospective sulcus limitans of the neural tube.